Victimization of ukrainian population: state, determinants, prevention - Головкін, Б. М. (Theory and practice of jurisprudence, 2016)
The article considers the concept of Ukrainian population victimization, its object, actors, flow trends. According to the MIA of Ukraine statistics, yearly more than 340 thousand people become crime victims, and the victimization coefficient is 75 individuals per 10,000 population. However, our poll has found that 37 % of the population become crime victims or 170 000 citizens. Under our data, 38 % individuals suffered from crimes against property, 21 % – against the person, 15 % – against individual rights, 9 % – from the crimes in the sphere of economic activity, 8 % – from computer systems and computer networks crimes, and the rest-from other crimes. Most often, citizens have been victims of theft, hooliganism, corruption, fraud, body harm, illegal intervention in the digital operations. Among the group (mass) victimization determinants are named: underdevelopment of citizens safe behavior in everyday life, fear of crime, common traditions of avoiding law enforcement authorities for protection from criminal attacks, concealing the committed crimes. The phenomenon of victimhood institutionalization, namely getting used to the consequences of crime and related psychological readiness of the significant part of the population to suffer from criminal offenses, possesses a special place . The determinants of personal victimization are victimogenic personal deformations, particularly: a set of negative socio-psychological characteristics of personality, that resulted from unfavorable socialization conditions. It comes to the poor adaptability to social and legal norms, the problems in communication, 2 uncritical thinking and lack of ability to predict the development of events, inappropriate behavior in crisis situations. Victimological warning is an independent branch of crime prevention, which includes a range of measures and activities aimed at reducing the level of individual and group victimization, as well as reducing the number of crime victims in society. Key words: victimhood, victimization, victimization determinants, victimological prevention.